2009
DOI: 10.4049/jimmunol.0900420
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Presentation of IL-15 by Intestinal Epithelial Cells Drives Development of CD8αα IELs

Abstract: IL‐15, which is trans‐presented by IL‐15Rα+ cells to neighboring IL‐2Rβ/γC+ cells, is crucial for the development of intestinal intraepithelial lymphocytes (IEL). Parenchymal cells have a major role in the trans‐presentation of IL‐15 to IELs; however, the specific identity of this cell type is unknown. Since trans‐presentation requires cell‐cell contact, we hypothesize that intestinal epithelial cells (IEC) are the parenchymal cell trans‐presenting IL‐15 to IELs. To determine whether IECs trans‐present IL‐15 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(137 citation statements)
references
References 40 publications
5
131
0
Order By: Relevance
“…4b) in the Arnt f/f -CD4 and control mice. IL-15 is a critical cytokine for the development of IELs 13,18,19 . Previous studies indicated that treatment of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells with IL-15 increased the expression of CD8aa 19,20 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4b) in the Arnt f/f -CD4 and control mice. IL-15 is a critical cytokine for the development of IELs 13,18,19 . Previous studies indicated that treatment of CD4 À CD8 À TCRb þ NK1.1 À B220 À CD5 þ cells with IL-15 increased the expression of CD8aa 19,20 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-15 is critical for the development of TCRab þ CD8aa þ IELs 18,19 . The role of IL-15 in the development of TCRab þ CD8aa þ IELs was suggested by the observation that IL-15 could support the expression of CD8a by the precursors of TCRab þ CD8aa þ IELs in vitro 19,20,23 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that mouse epithelial or keratinocyte cell lines could replace such cell-cell contacts, and may provide a microenvironment that supports gd iIEL survival ex vivo. To test this hypothesis, we cocultured GFP high gd iIELs either with the intestinal epithelial cell line m-IC (cl2) or with the keratinocyte cell line PDV for a period of 7 d. Furthermore, GFP high gd iIELs were cultured with a mixture of the cytokines IL-2, IL-7, and IL-15, which have been reported to at least slightly prolong the ex vivo life span of isolated gd iIELs (26,27,(53)(54)(55)(56)(57). By FACS quantification of GFP + cells it quickly became evident that m-IC (cl2) cells were not supporting the ex vivo survival of sorted gd iIELs (Fig.…”
Section: Ccr9 Deficiency Hinders Gd Iiel Homing To the Intestinal Epimentioning
confidence: 99%
“…The opposing cells respond through the signaling components of an IL-15 receptor complex (IL-15R␤/␥C). 30 Despite studies identifying IL-15 transpresenting cells for NK, memory CD8 ϩ T cells, and intestinal intraepithelial lymphocytes, [31][32][33] the cell type(s) transpresenting IL-15 to iNKT cells has not been described. Prior studies using various IL-15R␣ bone marrow (BM) chimeras revealed IL-15R␣ expression by either hematopoietic or nonhematopoietic cells partially recovers peripheral NK1.1 ϩ T cell numbers.…”
Section: Introductionmentioning
confidence: 99%